2022
DOI: 10.1101/2022.02.08.479624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for RNA or protein transport from somatic tissues to the male reproductive tract in mouse

Abstract: The development of tools to manipulate the mouse genome, including knockout and transgenic technology, revolutionized our ability to explore gene function in mammals. Moreover, for genes that are expressed in multiple tissues or at multiple stages of development, the use of tissue-specific expression of the Cre recombinase allows gene function to be perturbed in specific cell types and/or at specific times. However, it is well known that putative tissue-specific promoters often drive unanticipated off target e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Crucially, miR-941 was also detected in embryos derived from pairings between miR-941-expressing males and wild-type females. Rinaldi et al (2023) most recently demonstrated that transgenic neural-and adipose-specific Cre recombinase mice, as well as AAV-mediated neural Cre expression, resulted in clear off-target recombination in the epididymis, and that this distal recombination involved transportation via the circulatory system using both parabiosis and either serum or serum-EV injections into reporter mice. Together, these data provide the first direct evidence that ncRNA transcribed in the soma can be shuttled inside EVs into animal gametes and even into the next generation (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Crucially, miR-941 was also detected in embryos derived from pairings between miR-941-expressing males and wild-type females. Rinaldi et al (2023) most recently demonstrated that transgenic neural-and adipose-specific Cre recombinase mice, as well as AAV-mediated neural Cre expression, resulted in clear off-target recombination in the epididymis, and that this distal recombination involved transportation via the circulatory system using both parabiosis and either serum or serum-EV injections into reporter mice. Together, these data provide the first direct evidence that ncRNA transcribed in the soma can be shuttled inside EVs into animal gametes and even into the next generation (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…There are also various reports regarding the sites of Cre activity in the reproductive organs. Some investigators have observed Cre activity in the testis, whereas others have reported Cre expression in the epididymis [ 7 , 26 , 27 ]. Conversely, James et al reported a decline in Nestin expression in epididymal cells as individuals grow, with significantly reduced expression observed in adults [ 25 ].…”
Section: Discussionmentioning
confidence: 99%